Linguistics Colloquium 58: Linguistic Diversity in the World and for the World - Volungevičienė, Skaistė; Šinkūnienė, Jolanta; Valiukienė, Vita (Vilnius University Proceedings, 2023)
The thematic area of this year’s Conference is linguistic diversity, which we understand as diversity of cultures, diversity of attitudes and values reflected in language, and opportunities for mutual understanding and cultural enrichment. Linguistic diversity is exciting not only as a phenomenon by itself, but also as an object of research, which makes it possible to draw interesting parallels from typological and comparative perspectives as well as to investigate individual languages and viewpoints expressed in them. Linguistic diversity is also closely connected with multilingualism, which emphasises the individual and communicative aspects of linguistic diversity. In many everyday situations people communicate in several languages. Multilingual individuals or groups are more the rule than the exception, which is especially relevant in the context of small countries and small languages. Multilingualism is a way to deal with linguistic diversity on an individual level, as linguistic diversity highlights the necessity of speaking more than one language in order to understand the world and human beings better. Therefore, the topic of linguistic diversity also embraces the possibilities of learning several languages.